(untitled) (Journal of actual problems of jurisprudence, 2019)
In conclusion, I would like to say that the legal regime of subsoil use contracts for today is characterized by underdevelopment, which is expressed in deficit and insufficient consistency of the legislation on subsoil. The degree of development of subsoil use contracts significantly inferior from the classical civil law contracts in the first place because the protracted scientific dispute over whether subsoil use contracts should be attributed to one of the types of civil contracts.